Genome-wide exploration of bZIP transcription factors and their contribution to alkali stress response in Helianthus annuus - Rahman, Shahroz (2023)
The basic leucine zipper (bZIP) gene family is one of the largest transcription factors family in plants. These are involved in various biological processes including the regulation of light signaling, seed maturation, flower development, and the response to both biotic and abiotic stresses. Despite the crucial role of this gene family, no comprehensive investigation has been carried out to characterize bZIPs in sunflower. Therefore, an in silico analysis along with a wetlab experimental approach was adopted for bZIPs in sunflower plants. During the study, 73 bZIPs were identified in sunflower. Phylogenetic analysis involving bZIPs from A. thaliana, H. annuus, C. arabica, L. sativa, and V. vinifera divided these members into 11 groups and testified using conserved motif and gene structure analysis. Protein-Protein interaction analysis identified five clusters of HabZIPs. Intron diversity ranged from 0 to 12. The cis-regulatory elements analysis predicted various stress-responsive elements. RNA-seq data analysis reveiled that clusters of bZIPs were involved in stress response in roots and leaves during early or late stages of plant growth. Similatly, qRT-PCR analysis identified that HabZIP01, 04, 18, and 48 were significantly upregulated in response to mild or svere salt stress. Conversely, HabZIP08 was downregulated in response to both levels of salinity. Overall the study provides new insights into stress-responsive HabZIP genes in sunflower and provides a foundation for further research on their role in the plant's response to abiotic stress.